Transformasi Sistem Pengolahan Pertanian dan Pola Kerja pada Petani Tembakau Tradisional Ke Modern di Desa Morobongo, Kecamatan Jumo, Kabupaten Temanggung - Wu, Aaron; Mariyono, Joko; Dalmiyatun, Tutik (Universitas Galuh, 2026)
Changes in agricultural processing systems and the work patterns of tobacco farmers in Morobongo Village reflect the dynamics of adaptation to agricultural modernization. This transformation is driven by technological advancements as well as economic, social, and ecological factors that push farmers toward greater efficiency and productivity. This study aims to analyze the shift from traditional to modern agricultural systems and identify the factors influencing this change. The research, conducted from December 2024 to January 2025, used a case study involving five farmer groups across four hamlets, with data collected through purposive sampling, in-depth interviews, observations, and documentation. Qualitative analysis was carried out through data reduction, thematic categorization, and interpretation. The results show that modernization offers substantial benefits, including reduced labor needs, faster planting processes, and increased yields. However, several challenges remain, such as limited capital, inadequate training, restricted access to machinery, and shortages of skilled human resources. Environmental issues, particularly declining soil fertility due to chemical inputs, also persist. Overall, the success of agricultural transformation requires not only technological availability but also sustained government support through training, subsidies, infrastructure development, and stronger farmer institutions. This study provides useful input for policymakers and offers empirical insight into farmers’ adaptive strategies amid ongoing agricultural change.